Análise das condições de conforto térmico sob baixas temperaturas em uma indústria de polpa de açaí na cidade de Abaetetuba-Pará - PINHEIRO, Andréia Lobato (2024)
Occupational exposure to low temperatures leads the human body to some physiological adaptations that directly interfere in their performance. This study aimed to prepare an analysis of the physical risks of workers in a acai pulp company in the municipality of Abaetetuba- Pa, proposing improvements needed in order to adapt the workplace to health and safety standards of the current work in country. The method used consisted of collecting data from on-site observation, photographic report and interviews. Through this interview he rose issues related to thermal comfort, health and worker performance. It was concluded that the lack of speed and the onset of numbness in the hands, are directly related to the lack of use of gloves, and discomfort in the feet is related to the use of boots are not suitable for working in a cold environment. In addition, workers to carry the product from the production area to the freezing tunnels and chambers frigorificais for product shipment, has been suffering from thermal discomfort caused by the temperature difference that exists in these locations.